Why Effective Communication is Important in Management of Public Health Emergencies – A Viewpoint - Ramachandran, Ganesh; Min, Aung Ko Ko (International Journal of Health Sciences, 2024)
Purpose: This article aims to present a reflective viewpoint of what entails effective communication and why it is important in a public health setting when dealing with emergencies. Methodology: The article uses the COVID 19 pandemic as a template to illustrate how effective communication is needed to address a public health emergency effectively. Findings: Centralized and non-conflicting communication is integral in ensuring effective management of a public health emergency. Effective management requires consistent, centralized, and simple to understand and implement communication. Unique Contribution to Theory Practice and Policy: Public Health Emergencies are national emergencies and require collaboration of multiple agencies and stakeholders to effectively address and control the situation. This process must ensure that the public who are the primary stakeholder receive the maximal benefits from any intervention to safeguard their health and safety while guaranteeing economic and social stability.